Seasonal Changes in Methanogenesis and Methanogenic Community in Three Peatlands, New York State - Sun, Christine L.; Brauer, Suzanna L.; Cadillo Quiroz, Hinsby; Zinder, Stephen H.; Yavitt, Joseph B. (Frontiers in Microbiology, 2012)
Fluctuating environmental conditions can promote diversity and control dominance in community composition. In addition to seasonal temperature and moisture changes, seasonal supply of metabolic substrates selects populations temporally. Here we demonstrate cascading effects in the supply of metabolic substrates on methanogenesis and community composition of anaerobic methanogenic archaea in three contrasting peatlands in upstate New York. Fresh samples of peat soils, collected about every three months for 20 months and incubated at 22+2oC regardless of the in situ temperature, exhibited potential rates of methane (CH4) production of 0.02 to 0.2 mmol L-1 day-1 (380 to 3,800 nmol g-1 [dry] day-1). The addition of acetate stimulated rates of CH4 production in a fen peatland soil, whereas addition of hydrogen (H2), and simultaneous inhibition of H2-consuming acetogenic bacteria with rifampicin, stimulated CH4 production in two acidic bog soils, especially, in autumn and winter. The methanogenic community structure was characterized using TRFLP analyses of SSU rRNA genes. The E2 group of methanogens (Methanoregulaceae) dominated in the two acidic bog peatlands with relatively greater abundance in winter. In the fen peatland, the E1 group (Methanoregulaceae) and members of the Methanosaetaceae were co-dominant, with E1 having a high relative abundance in spring. Change in relative abundance profiles among methanogenic groups in response to added metabolic substrates was as predicted. The acetate-amendment increased abundance of Methanosarcinaceae, and H2-amendment enhanced abundance of E2 group in all peat soils studied, respectively. Additionally, addition of acetate increased abundance of Methanosaetaceae only in the bog soils. Variation in the supply of metabolic substrates helps explain the moderate diversity of methanogens in peatlands.